Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Loyalitas Kerja Karyawan pada Mandiri Tunas Finance Medan 2 - Panjaitan, Yosua Boas Oliver; Yudhira, Ahmad; Pakpahan, Evalina (Jurnal Edueco, 2026)
This study aims to determine the influence of leadership style and work environment partially on employee work loyalty and the influence of leadership style and work environment simultaneously has a positive and significant effect on employee work loyalty at Mandiri Tunas Finance Medan 2. This study was conducted at Mandiri Tunas Finance Medan 2 with a population of all employees at Mandiri Tunas Finance Medan 2 as many as 43 people. The sampling technique in this study was total sampling so that the sample size in this study was 43 people. The results showed that the t-value of the leadership style variable was 2.473 and the t-table value was 2.021 and the sig-value was 0.018 and the sig-table value was 0.05. With the provisions of the t-value> t-table and the sig-value <sig-table or (2.473> 2.021) and (0.018 <0.05). the t-value of the work environment variable is 4.722 and the t-table value is 2.021 and the sig value is 0.000 and the sig-table value is 0.05. With the provision that the t-value> t-table and the sig-value <sig-table or (4.722> 2.021) and (0.000<0.05). with the F-value of the leadership style and environment variables is 32.660 and the F-value of 3.23 and the sig value (0.000> 0.05) and the R2 Square value is 62.0%, meaning that the independent variables in this study only have an influence of 62.0% while the remaining 38.0% is influenced by other factors outside this study. The conclusion of this researcher is that Leadership Style has a positive and significant partial effect on employee work loyalty at Mandiri Tunas Finance Medan 2, the work environment has a positive and significant effect on employee work loyalty at Mandiri Tunas Finance Medan 2 and leadership style and work environment have a positive and significant simultaneous effect on employee work loyalty at Mandiri Tunas Finance Medan 2.